THEORY OF LABOR LAW IN THE CONTEXT OF METHODOLOGICAL PROBLEMS - Вишновецька, С. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2008)
The article deals with the theoretical positions of the science of labor law in the methodological aspect.